Influence of tank’s wall displacements measurement error on its internal stressed state determination - Паньків, Христина Василівна (Eastern-European Journal of Enterprise Technologies, 2015)
In the article the tank’s wall surface coordinates measurement error was calculated and its influence on the accuracy of the tank’s wall material stress-strain state determination was shown. Possible approaches to reduce error are also shown, such as increasing precision of angular positioner’s encoder wheel and using a camera with higher resolution. The measurement error dependence on the tank’s base radius and the number of the measurement points are shown and a conclusion was drown, that more measurement points should be chosen to achieve required accuracy for bigger tank’s base radius. Reducing of tank’s wall surface coordinates measurement error influence on tank’s stress-strain state accuracy calculation is provided with using smoothing splines. The principles for measuring tank’s wall surface coordinates, developed by author provides high accuracy levels and are good enough for using them to estimate the tank’s wall stress-strain state.